Comparison between brazilian education and that of countries with good results in the PISA exam: A study based on TALIS - Silva, Alexsander Figueiredo; Hoed, Raphael Magalhães; Saraiva, Pedro Fabio (Seven Editora, 2023)
Brazil has obtained poor results in basic education compared to other countries, especially developed ones. One of the most important actors in the education process are the teachers. The Teaching and learning international survey (TALIS), coordinated by the Organization for Economic Cooperation and Development (OECD), provides relevant information about the learning environment and working conditions of basic education professionals. This article proposes a study on TALIS, comparing Brazilian basic education with that of well-ranked countries in the examination of the Program for International Student Assessment (PISA) and verifying how adjusted Brazilian basic education is to the best international practices. The Apriori algorithm was used to mine the rules of association, allowing the investigation of which factors are associated with the improvement of education in high school institutions in the perception of the teaching public. DOI:https://doi.org/10.56238/ptoketheeducati-069